A book of coupons - Morgenstern, Susie Hoch.; Bloch, Serge; Rosner, Gill (New York : Puffin Books, 2003)
Elderly Monsieur Noel, the very unconventional new eighth-grade teacher, gives coupon books for such things as dancing in class and sleeping late, which are bound to get him in trouble with the military discipline of Principal Incarnation Perez.
"First published in France in 1999 by L'ecole des loisirs under the title Joker"--T.p. verso.
Translation of: Joker.
Book Links (A.L.A.).
Notable/Best Books (A.L.A.).
Wilson's Children.
5.1
Keywords: Humorous stories; Schools -- Fiction; Teachers -- Fiction; Humorous fiction; School stories; Teachers -- Fiction